O Jovem e o ensino de História: a construção da concepção de história por alunos do ensino médio - Joana D'arc Germano Hollerbach (2007)
This research had as a goal to identify what conceptions the youngsters who were graduating from High School have regarding History and to what extent History may have contributed to the elaboration of these same conceptions throughout Basic Education; and also other spaces which could be identified as factors of influence on these conceptions. A total of 170 participants, students of the third year of High School (Ensino Médio) who were distributed in 5 public and private schools in Governador Valadares, and the school counselors as well. The data were collected through a questionnaire and interviews, and also statistical data were searched in official parties (INEP, MEC, and IBGE). The data related to the municipality of Governador Valadares were obtained from the Socio-economic Diagnostic of the city, which was elaborated by Faculty of Administration of Governador Valadares in a partnership with the IPEAD (Institute for Research in Economics, Management and Accounting of Minas Gerais). The analysis of data was established based on authors who investigate issues related to youth, among them are Dayrell (2002; 2003; 2006), Sposito (1997; 2003); and the teaching of History such as Siman (2001; 2003), Pais (1999), Carretero (1997) and others. At the end of the research we could perceive that despite the socio-economic conditions that distinguish the subjects, it was not possible to identify significant indications of social environment interference on the construction of youngsters conceptions in the research throughout basic education. We view school as a space that overlaps with other spaces in the construction of the historical knowledge of youngsters and their conceptions of history. The great majority presents a conception which resembles a traditional perspective on the comprehension of history. A minor group indicates, otherwise, a more problematic and critical conception of history. The predominance of a more traditional conception, judging by the statements of the coordinators/counselors who were interviewed, might be related to the existence of practices which are not so instigating, still present in the schools which the formed the data sample.